2016
DOI: 10.19173/irrodl.v17i5.2523
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Culture and OER Policy: How Structure, Culture, and Agency Mediate OER Policy Potential in South African Universities

Abstract: Several scholars and organizations suggest that institutional policy is a key enabling factor for academics to contribute their teaching materials as open educational resources (OER). But given the diversity of institutions comprising the higher education sector-and the administrative and financial challenges facing many institutions in the Global South-it is not always clear which type of policy would work best in a given context. Some policies might act simply as a "hygienic" factor (a necessary but not suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 16 publications
2
32
0
6
Order By: Relevance
“…In their study of institutional culture and OER policy, Cox and Trotter (2016) found that appropriate institutional policies alone cannot ensure sustainable engagement with OER: "institutional culture mediates the role that policy plays in academics' decision making." The same appears to be true for OEP.…”
Section: Discussionmentioning
confidence: 99%
“…In their study of institutional culture and OER policy, Cox and Trotter (2016) found that appropriate institutional policies alone cannot ensure sustainable engagement with OER: "institutional culture mediates the role that policy plays in academics' decision making." The same appears to be true for OEP.…”
Section: Discussionmentioning
confidence: 99%
“…• This broad and critical conceptualisation of OEP has been cited by many OEP researchers (see Arinto, et al, 2017;Cox & Trotter, 2016;Cronin, 2017;Czerniewicz, et al, 2017aCzerniewicz, et al, , 2017bNerantzi, 2017;and Paskevicius, 2017).…”
Section: Iv) Cilt (Centre For Innovation In Learning and Teaching) Uctmentioning
confidence: 93%
“…It is not clear whether buy-in can be interpreted as the need for a relevant policy or just support. Other research suggests an intellectual property policy itself is more hygienic rather than a motivating factor, and that it is the culture that influences academics' decisions (Cox & Trotter, 2016).…”
Section: Discussionmentioning
confidence: 99%